Evaluating improvement in acute stroke management following pre-hospital initiation of acute stroke service - Jessica AN,; Wan Asyraf Wan Zaidi,; Nik Azlan Nik Muhamad, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Prehospital notification of the stroke team in alerting incoming acute stroke patient has been practiced in several countries worldwide. Currently this is not practiced in Malaysia. This study evaluates feasibility and impact to stroke team door to review time when prehospital notification is employed. Duration of case control study was between June 2018 to January 2019. Control phase consists of conventionally activating stroke team after in-hospital assessment by emergency medical officer. This was then followed by an intervention phase where on scene activation of stroke team was done by the Prehospital Emergency Care (PHC) staff. Training of PHC staff in recognising an acute stroke was based on identification of BE-FAST (Balance, Eyes, Face, Arm and Speech Test) abnormalities. The objectives were to compare the mean between two groups for acute stroke team review time, door to computerised tomography (CT) scan and door to thrombolysis time. Thirty-nine patients were analysed (control n=29, intervention n=10). Results were insignificant (p>0.05). Mean time in minutes for control phase vs. intervention phase was as follows: Door to stroke team review time, 25.96 + 39.16 vs. 15.9 + 13.14, door to CT scan was 43.04 + 40.00 vs. 25.8 + 11.35. Only 3 patients underwent thrombolytic therapy during study period. Limitation was non-parametric data with lack of number of acute stroke cases responded during the intervention period. With continual training of pre-hospital staff in detecting acute stroke, feasibility can be improved.